Acessibilidade e mobilidade nos passeios públicos da cidade de Santa Maria, RS - Müller, Ana Paula Soares (2022)
Based on the consideration that, when moving around cities, all individuals are pedestrians at some point of the way, accessibility is a fundamental characteristic to ensure the mobility of all people through pedestrian spaces. However, problems and obstacles are often observed in the infrastructure of public sidewalks and crosswalks with regard to accessibility, which can mean usage and mobility limitations and impediments for people, especially those with disabilities. In the city of Santa Maria the reality is no different, and knowing the conditions of sidewalks, focusing on accessibility, is essential in order to allow people with disabilities to use them autonomously, safely, comfortably, and in equal conditions with other people. Therefore, the proposed research aims to evaluate the accessibility of sidewalks and crosswalks in the central region of the city to ensure mobility and equal use by people with physical, visual, and hearing disabilities. Understanding the perception of the target audience, through survey and accompanied walks, and knowing the characteristics of the public sidewalks and crosswalks in the city center, through site mapping with an evaluation checklist, it is expected to grade the conditions that most affect the accessibility of these places for these people, generating accessibility indexes and promoting improved access and social inclusion. According to the results obtained, the survey and the accompanied walks revealed the negative and dissatisfied perception of people with disabilities who circulate on the sidewalks in the region, highlighting the problems and obstacles of accessibility that they observe in these places. The evaluation checklist allowed to identify the mostly precarious conditions of these spaces, including sidewalk with holes and unevenness, lack of tactile paving, furniture and urban elements blocking the circulation, and crosswalks and curb ramps in bad conditions. Through the classification of problems and obstacles and the elaboration of accessibility indexes for sidewalks and crosswalks, it was also possible to identify the low level of accessibility that these spaces offer in the perception of people with disabilities, highlighting the lack of accessibility in these places. Hence, the importance of ensuring accessibility in circulation spaces for the mobility of pedestrians with disabilities is highlighted, and it is hoped that the results found in this study will foster the discussion and reflection about this issue.